Comparison of Real Development Levels of Countries – Genesis and Perspectives - Prekajac, Zora (Panoeconomicus, 2007)
Comparison of levels of development among countries is usually done by reducing values in national currencies with a common denominator, using the official exchange rate. Because of its unreality, the values calculated in this way do not illustrate real relations between compared countries. That brings about the launching of the UN International Comparison Project (latter Programme) with two fold aims: developing a method for international comparison of real domestic product which could be applied to a number of very heterogeneous countries, and the comparison of growing number of very different countries. Until now six phases of comparisons are finished. Taking into consideration problems that appeared in the realization of the VI ICP phase as well as quality improvement proposals, a decision has been made to launch a new, global round for 2003-2006. Comparison will cover 150 countries (the widest coverage ever). This will give global character to the comparison, which was the end cause of the ICP. Key words: Comparison, Real GDP, Purchasing power parity, ICP. JEL: E01, F01, I30.